HOW NOT TO WORK AND PLAY WITH OTHERS: AN UPDATED TAXONOMY OF DYSFUNCTIONAL INDIVIDUAL BEHAVIORS IN GROUPS. Issue 2 (February 2016) - Kolb, Judith A.
Abstract : Much of what we do in today's organizations involves working collectively in groups or teams. Certain individual behaviors hinder this effort. In this article, the author proposes a taxonomy of dysfunctional individual group member behaviors that is informed by the much‐cited list of self‐serving behaviors proposed by Benne and Sheats in 1948. This taxonomy identifies six individual dysfunctional behaviors using the categories of personal relating, power, and performance.